1996
DOI: 10.2307/2410858
|View full text |Cite
|
Sign up to set email alerts
|

Parental Effects in Plantago lanceolata L. I.: A Growth Chamber Experiment to Examine Pre- and Postzygotic Temperature Effects

Abstract: Lacey, E. P. (1996) Parental effects in Plantago lanceolata. L. I. A growth chamber experiment to examine pre-and post-zygotic temperature effects. Evolution 50(2): 865-878. In spite of the potential evolutionary importance of parental effects, many aspects of these effects remain inadequately explained. This paper explores both their causes and potential consequences for the evolution of life-history traits in plants. In a growth chamber experiment, I manipulated the pre-and postzygotic temperatures of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
140
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(153 citation statements)
references
References 55 publications
10
140
1
2
Order By: Relevance
“…Sampling mature individuals also reduced any potential influence of parental effects on offspring phenotype, which are generally more prevalent in juvenile life-history stages relative to adult life-history stages (Roach & Wulff 1987;Weiner et al 1997). This is consistent with studies of P. lanceolata where parental temperature influences germination, growth and reproduction of newly germinated seeds but not survival or reproduction of offspring after 1 year (Lacey 1996;Lacey & Herr 2000). To further reduce any potential influence of parental environment on offspring phenotype, sampled individuals were grown in separate pots in watered and fertilized medium in a glasshouse at Syracuse University, New York, USA, for 6 months before propagation.…”
Section: O M M O N G a R D E N T R A I T M E A S U R E M E N T Ssupporting
confidence: 83%
“…Sampling mature individuals also reduced any potential influence of parental effects on offspring phenotype, which are generally more prevalent in juvenile life-history stages relative to adult life-history stages (Roach & Wulff 1987;Weiner et al 1997). This is consistent with studies of P. lanceolata where parental temperature influences germination, growth and reproduction of newly germinated seeds but not survival or reproduction of offspring after 1 year (Lacey 1996;Lacey & Herr 2000). To further reduce any potential influence of parental environment on offspring phenotype, sampled individuals were grown in separate pots in watered and fertilized medium in a glasshouse at Syracuse University, New York, USA, for 6 months before propagation.…”
Section: O M M O N G a R D E N T R A I T M E A S U R E M E N T Ssupporting
confidence: 83%
“…While the latter source is nongenetic in the strict sense, persistent intergenerational environmental effects among clonal modules indicate that this "somatic memory" (Schwaegerle et al 2000) yields variation that is effectively heritable and available to selection processes acting on clonal offspring. It may have further evolutionary consequences if phenotypic responses to intergenerational environmental variance are genotype specific or environmentally induced variation becomes fixed within propagative cells (Lacey 1996).…”
Section: Heritability Of Intraclonal Variationmentioning
confidence: 99%
“…Greenhouse and growth-chamber studies show that the environment during fertilization and early embryonic development of an offspring while still attached to the maternal parent can influence offspring seed mass and germination (e.g., Riddell and Gries 1958, Koller 1962, Robertson et al 1962, Sawhney and Naylor 1979, Gutterman 1980, Siddique and Goodwin 1980, Wulff 1986, Case et al 1996. It can also influence offspring fitness in the field (Lacey and Herr 2000). The studies cited here examined the specific effects of postzygotic temperature and/or photoperiod on off-spring traits.…”
mentioning
confidence: 99%
“…Our study was motivated by Lacey and Herr's (2000) observation that postzygotic temperature can influence offspring fitness in field-grown P. lanceolata. Using two parental temperature regimes that resemble mean monthly temperatures for May and July, during which time P. lanceolata flowers in North Carolina, Lacey and Herr observed that high postzygotic temperature increased offspring fitness by almost 50%.…”
mentioning
confidence: 99%